Impact of entrepreneurial orientation and ESG on environmental performance: moderating impact of digital transformation and technological innovation as a mediating construct using Sobel test - Uma Shankar Yadav; Indrajit Ghosal; Anupam Pareek; Kritika Khandelwal; Ajay Kumar yadav; Chandra Chakraborty (Journal of Innovation and Entrepreneurship)
Abstract The purpose of this study is to analyze the impact of dimension of dynamic capabilities such as Entrepreneurial orientation (EO), technological innovation (TIN), and digital transformation (DT) and dimension of Stakeholder environment, society, and governance (ESG) practices on environmental performance (EP) in the handicraft industry. This study also investigates the mediating impact of dynamic capabilities such as Technological innovation (TIN) and Entrepreneurial orientation between ESG and EP and has applied the Sobel test. This study also checks the moderating impact of Digital transformation (DT) on EP through TIN. The Sobel test is most suitable for mediation analysis, whether partial or complete mediation. For this study, exploratory research methods , convenience sampling, and tools used a 5-point Likert scale. Therefore, the study was well suited to this type of experimental research, since it used the PLS–SEM path coefficient algorithm and PCA analysis software to examine several correlations simultaneously. A total of 150 respondents participated in this survey who were artisan’s new entrepreneurs and firm owners in the handicraft industry. Because of their outsized influence on emissions worldwide and consumption of resources, businesses worldwide have a responsibility to ensure environmental stability while also working to improve their practices to improve the craft industry as part of the small industry. These findings prove that by adopting ESG principles and Entrepreneurial orientation, the impact of technological innovation supports the environment's performance. The development of eco-friendly goods and procedures, the enhancement of craft productivity, and the evolution of sustainable development strategies are all greatly aided by digital transformation, technological innovation handicraft business environmental sustainability in the face of the escalating difficulties brought on by climate change. For verification and exploration of entrepreneurial orientation, technological innovation, Environmental performance, and environmental social and governance (ESG), this study is supported by the Dynamic capability theory (DCT), stakeholder theory, and especially ESG criteria. The research shows that firms' environmental performance can be significantly improved by emphasizing ESG factors and embracing technological advancements and entrepreneurial orientation.